Odpowiedzi

Najlepsza Odpowiedź!
  • ja14
  • Początkujący
2010-01-13T19:10:47+01:00
1{y=-2x+2
{4(-2x+2)+3=-12

y=-2x+2
-8x+8+3=-12

y=-2x+2
-8x=-12-8-3

y=-2x+2
-8x=-23

y=-2x+2
x~~2,88

y=-5,76+2
x~~2,88

y=-3,76
x~~2,88
zaraz podam drugi przyklad :)

22.
{y - 3x +4 = 0
{4 = x

{y-12=-4
{x=4

{y=8
{x=4

:)
1 5 1
2010-01-13T19:43:36+01:00
Y=-2x+2
4(-2x+2)+3=-12

y=-2x+2
-8x+8+3=-12

y=-2x+2
-8x=-12-8-3

y=-2x+2
-8x=-23

y=-2x+2
x=23/8
podstawiam
y=-23/4+2
x=23/8

y=-31/4
x=23/8

2.
{y - 3x +4 = 0
{4 = x
[podstawiam
{y-12=-4
{x=4

{y=8
{x=4